Calcium-permeable AMPA receptors in the VTA and nucleus accumbens after cocaine exposure: when, how, and why? - Wolf, Marina E.; Tseng, Kuei-Yuan (Frontiers in Molecular Neuroscience, 2012)
In animal models of drug addiction, cocaine exposure has been shown to increase levels of calcium-permeable AMPA receptors (CP-AMPARs) in two brain regions that are critical for motivation and reward - the ventral tegmental area (VTA) and the nucleus accumbens (NAc). This review compares CP-AMPAR plasticity in the two brain regions and addresses its functional significance. In VTA dopamine neurons, cocaine exposure results in synaptic insertion of high conductance CP-AMPARs in exchange for lower conductance calcium-impermeable AMPARs (CI-AMPARs). This plasticity is rapid (hours), GluA2-dependent, and can be observed with a single cocaine injection. In addition to strengthening synapses and altering Ca2+ signaling, CP-AMPAR insertion affects subsequent induction of plasticity at VTA synapses. However, CP-AMPAR insertion is unlikely to mediate the increased dopamine cell activity that occurs during early withdrawal from cocaine exposure. Within the VTA, the group I metabotropic glutamate receptor mGluR1 exerts a negative influence on CP-AMPAR accumulation. Acutely, mGluR1 stimulation elicits a form of LTD resulting from CP-AMPAR removal and CI-AMPAR insertion. In medium spiny neurons (MSNs) of the NAc, extended access cocaine self-administration is required to increase CP-AMPAR levels. This is first detected after approximately a month of withdrawal and then persists. Once present in NAc synapses, CP-AMPARs mediate the expression of incubation of cue-induced cocaine craving. The mechanism of their accumulation may be GluA1-dependent, which differs from that observed in the VTA. However, similar to VTA, mGluR1 stimulation removes CP-AMPARs from MSN synapses. Loss of mGluR1 tone during cocaine withdrawal may contribute to CP-AMPAR accumulation in the NAc. Thus, results in both brain regions point to the possibility of using positive modulators of mGluR1 as a treatment for cocaine addiction.